2023
DOI: 10.21203/rs.3.rs-2626591/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early-stage volume losses in the corpus callosum and thalamus predict the progression of brain atrophy in patients with multiple sclerosis

Abstract: A method that can be used in the early stage of multiple sclerosis (MS) to predict the progression of brain volume loss (BVL) has not been fully established. Thus, to develop a method of predicting progressive BVL in patients with MS (pwMS), eighty-two consecutive Japanese pwMS—with either relapsing-remitting MS (86%) or secondary progressive MS (14%)—and 41 healthy controls were included in this longitudinal retrospective analysisover anobservational periodof approximately 3.5 years. Using a hierarchical clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…In our previous study, we utilised a hierarchical cluster analysis with multivariate imaging data obtained by FreeSurfer analysis and classified cross-sectionally patients with MS into three clusters (Clusters 1, 2, and 3) in ascending order by disability and BVL at baseline [ 28 ] and follow-up [ 22 ]. Among patients included in Cluster 1 at baseline, approximately one-third of patients transitioned into Cluster 2 at follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we utilised a hierarchical cluster analysis with multivariate imaging data obtained by FreeSurfer analysis and classified cross-sectionally patients with MS into three clusters (Clusters 1, 2, and 3) in ascending order by disability and BVL at baseline [ 28 ] and follow-up [ 22 ]. Among patients included in Cluster 1 at baseline, approximately one-third of patients transitioned into Cluster 2 at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients included in Cluster 1 at baseline, approximately one-third of patients transitioned into Cluster 2 at follow-up. Baseline volumes of the corpus callosum, thalamus, and whole brain, excluding the volume of the ventricles, were significantly reduced in the transition group when compared with those in the nontransition group and were identified as the most important predictors of transition [ 22 ]. Conversely, in the current study, we found that the rate of whole-brain atrophy could be easily obtained in routine clinical practice using icobrain ms, which could be another good prognostic predictor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It serves as a relay center for primary sensory input to the cortex, facilitates movement and motor functional processing, and participates in higher cortical functions such as arousal, executive function, learning, memory, emotion, motivation, language, and multisensory integration (Schmahmann 2003). The thalamus and, specifically, its component nuclei have been implicated in several neurological, neuropsychiatric, and neurodegenerative conditions including essential tremor, multiple sclerosis, epilepsy, obsessive-compulsive disorder, schizophrenia, chronic pain syndrome, Alzheimer’s disease, and frontotemporal dementia (Neudorfer et al 2024; Fujimori and Nakashima 2024; Burdette, Patra, and Johnson 2024; Yang et al 2024; Alemán-Gómez et al 2023; Wang et al 2023; Forno et al 2023; McKenna et al 2023; Bernstein et al 2021; Low et al 2019). Until recently, the thalamus has been considered as a “whole” in most neuroimaging studies.…”
Section: Introductionmentioning
confidence: 99%